Perceptions of stress and resilience among Latina women enrolled in prenatal care in Metro Atlanta through an ecosocial lens. (23rd March 2021) - Stanhope, Kaitlyn K.; Comeau, Dawn L.; Ulloa, Monica; Leon, Juan S.; Suglia, Shakira F.; Hogue, Carol J. R.; Kramer, Michael R.
Abstract: Stress across the life course is highly prevalent, particularly among immigrant and racial/ethnic minority women who face adversities associated with structural and interpersonal racism. Understanding how women perceive and describe stress and resilience can provide cultural context to inform interventions to improve health among pregnant women facing adversity. The goal of this project was to examine how external stressors and coping strategies prior to and during pregnancy are reflected in Latina women's narratives about their lives through an Ecosocial framework. This mixed methods research study explores pregnant Latina women's psychosocial well‐being before and during pregnancy based on Ecosocial theory. We conducted 111 surveys with Latina women receiving prenatal care in Atlanta, Georgia in 2017–2018. We conducted 24 in‐depth interviews, chosen purposively from survey respondents, collecting narratives of stress and resilience over the course of pregnancy. We purposively sampled equal numbers of women who did and did not report an ongoing stressor in the survey. The survey and interview guide were focused on domains of stress, psychosocial being, coping and resilience. The majority of survey participants spoke Spanish (86%) and were born in Mexico (42%) or Guatemala (27%). Less than half (37%) reported ongoing stress, most commonly from a loved one's illness or work‐related problem. The majority of women felt they should control emotional responses to external stressors during pregnancy to protect their baby's health. Women described motherhood and previous challenges as sources of maturity and improved coping. Familial financial and emotional support were perceived as critical to women's successful coping.